2006
DOI: 10.1002/humu.9397
|View full text |Cite
|
Sign up to set email alerts
|

A rare missense mutation in a type 2 diabetes patient decreases the transcriptional activity of human sterol regulatory element binding protein-1

Abstract: Sterol regulatory element binding protein 1 (SREBP-1) transcription factors play a key role in energy homeostasis by regulating genes involved in both carbohydrate and lipid metabolism, and in adipocyte differentiation. The 5' end of the mRNA-encoding SREBP-1 exists in two forms, designated 1a and 1c. The divergence results from the use of two transcription start sites that produce two separate 5' exons, each of which is spliced to a common exon 2. Mutations in the sterol regulatory element binding protein gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Protein analysis was carried out by Western blot as previously described [10] using antibodies to EGR‐1 (Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Protein analysis was carried out by Western blot as previously described [10] using antibodies to EGR‐1 (Santa Cruz Biotechnology, Santa Cruz, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In all the studies described above, no functional data concerning the variants identified were provided. Vernia et al [90] have described the first SREBP-1 mutation found in a type 2 diabetic patient that modifies the function of the protein, diminishing its DNA binding efficiency and its ability to activate the transcription of target genes. Unfortunately, family data were not available for cohort studies and it is thus difficult to directly relate the observed mutation and the type 2 diabetes of the patient.…”
Section: Srebp-1c: Clinical Perspectivesmentioning
confidence: 99%